Diseño e implementación de un sistema utilizando la metodología XP para la unidad de administración de talento humano de la Universidad Técnica De Cotopaxi - Aimacaña Toapanta, Oswaldo (2012)
The system has been developed based on the requirements described by who works in the Unit of Administration of Human Talent, through the constant dialogue and revision followed by the advances of the system to obtain a System free of errors, efficient and robust. This project has as purpose to contribute from a significant way to the treatment of the information in the reception process, analysis and tabulation of data. The system has been developed in language HTML, with the combination of other more languages as PHP 5.2.6, CSS, JavaScript, XML. To the being of open code, the interfaces and bookstores can be modified freely by different graphic editors of these languages. This package of languages has been chosen by its correct form of work, its simplicity and good yield. Also because to the being a System Web, to the being installed in the servant, it can be used by several users in different PCS in the Intranet of the Institution or in the Internet. The data are kept in one of the motors of databases leader in the software development, MySQL 5.0, software obtained of Internet and of gratuitous license.